The global financial crisis: effects on Bolivia - Luis Carlos Jemio M.; Osvaldo Nina (Institute for Advanced Development Studies (INESAD), 2009)
The global financial crisis is expected to have a negative impact on the Bolivian economy. Effects will transmit into the economy through lower export prices and quantities, reduced amount of remittances and depressed foreign direct investment (FDI) flows. These shocks will bring about deficits in the current account and fiscal balances, foreign exchange reserves losses, sluggish economic growth and higher unemployment rates. The latest data available show that the economy is already experiencing the effects of the economic downturn, in the form of decreased exports revenues, sharp reductions in the rates of growth of foreign of exchange reserves and bank lending and a tendency towards a re-dollarisation of financial assets and liabilities. The Bolivian economy, however, is better prepared, at least in the short run, to cope with the negative effects of the crisis. The commodity export boom experienced between 2005 and 2008 has permitted the country to run sizable external and fiscal surpluses and accumulate foreign exchange reserves. The financial system has exhibited more prudent behaviour in recent years, by not expanding credit too much and increasing investments in highly liquid public bonds. Therefore, although banks are expected to be affected by the global financial crisis, they have high liquidity ratios and are not extremely exposed to risk. The capacity of the Bolivian economy to offset the negative effects of the global crisis will depend on several factors, such as the severity and duration of the crisis and, above all, the quality of the policies that policymakers will implement to cope with the crisis. The government faces several trade-offs in implementing policies in order to cope with the effects of the crisis. The central bank, for instance, is committed to maintaining a fixed exchange rate, in order to reduce inflationary pressures and to avoid a re-dollarisation of the financial system. However, a fixed exchange rate policy has already brought about an exchange rate appreciation, which is hurting competitiveness of tradable activities. Furthermore, the government has room to implement countercyclical fiscal policies, by resorting to the deposits accumulated in the central bank during the export boom years. During 2009, the government is planning to expand public investment and to increase direct transfers to the population. However, these policies are not likely to offset the negative effects that the crisis will have on growth and employment. More efforts should be made to improve the quality of public spending, in order to maximise its impact on economic growth, employment creation and poverty reduction.
Keywords: 330